Basic and applied aspects of biotechnology - Gupta, Varsha, 1966-; Sengupta, Manjistha; Prakash, Jaya (Springer, 2017)
This book explores the journey of biotechnology, searching for new avenues and noting the impressive accomplishments to date. It has harmonious blend of facts, applications and new ideas. Fast-paced biotechnologies are broadly applied and are being continuously explored in areas like the environmental, industrial, agricultural and medical sciences. The sequencing of the human genome has opened new therapeutic opportunities and enriched the field of medical biotechnology while analysis of biomolecules using proteomics and microarray technologies along with the simultaneous discovery and development of new modes of detection are paving the way for ever-faster and more reliable diagnostic methods. Life-saving bio-pharmaceuticals are being churned out at an amazing rate, and the unraveling of biological processes has facilitated drug designing and discovery processes. Advances in regenerative medical technologies (stem cell therapy, tissue engineering, and gene therapy) look extremely promising, transcending the limitations of all existing fields and opening new dimensions for characterizing and combating diseases.
Keywords: Biotechnology.; elektronické knihy; electronic books